PEMODELAN DAMPAK PERUBAHAN LAHAN TERHADAP DEBIT BANJIR PADA DAS MENINTING DENGAN HEC-HMS - MUH BAGUS BUDIANTO; ATAS PRACOYO; HARTANA HARTANA; EKO PRADJOKO (GANEC SWARA, 2023)
Changes in land use in a developing area are difficult to avoid, including in watersheds which result in increased flood discharge. The Meninting River is one of the important rivers on the Lombok island which is experiencing relatively rapid land change. The purpose of this study was to determine the effect of land use change on flood discharge in the Meninting Watershed. The data needed is in the form of watershed maps, rainfall data, land use data and soil types. Land use maps were obtained from the results of Google Earth analysis for 2012, 2017 and 2022. The simulation uses daily rainfall data. The results of the design rain analysis are distributed into hourly rain using the Mononobe method. Data on soil types and land use are used to calculate the CN (curve number) value. Flood analysis using HEC-HMS software.The results of research using various return periods, namely 2 year, 5 year, 10 year, 25 year, 50 and 100 year return period, show an increase in CN values by 0.26% in 2017 and 1.22% in 2022. Changes in land use the land causes an average increase in flood discharge by 0.41% in 2017 and 1.19% in 2022.